"The Next Generation of International Law: Space, Ice, and the Cosmolegal Proposal" - Cirkovic, Elena (German Law Journal, 2021)
With the increasing environmental degradation in spaces most affected by climate change such as the Arctic, and the extension of anthropogenic environmental problems even into the Earth's orbit, international law is confronted with some unprecedented challenges. Much of the legal dialogue surrounding this question is taking place in the abstract, such that there are no exact proposals for methodological and practical applications in lawmaking. In this Article, I argue that current governance relevant to the Arctic and outer space precedes an understanding of these spaces. Critical posthumanism, and other approaches, point out the continuation of strict boundaries that have been set up between the human body and the environment. International law's formalist doctrinal deductions exacerbate these boundaries. I propose an approach to lawmaking under a broad term: the cosmolegal. The cosmolegal proposal challenges distinctions between human-made and non-human "laws"-scientific and social laws-and questions the foundational determination of both. The framework I suggest in this Article, therefore, requires a new approximation to accuracy in lawmaking, which could be achieved by greater interdisciplinarity and acceptance of ontological pluralism. This Article is divided into two broader sections. The first section focuses on two environmental problems: A) greenhouse gas (GHG) emissions in the Arctic and B) orbital debris. The second section argues for a different ontology of law and human self-understanding in the context of the unknown. It proposes "cosmolegality" in an attempt to approximate the inclusion and representation of 'everything considered to be non-human. Peer reviewed